Gereja Partisipatif-Memasyarakat di Tengah Pandemi Covid-19 - Yetva Softiming Letsoin; Antonius Deni Firmanto; Nanik Wijiyati Aluwesia (Media (Jurnal Filsafat dan Teologi), 2021)
The essay discusses the concept of the participatory and socially oriented Church in the midst of the Covid-19 pandemic. This topic departs from the reality that the Covid-19 pandemic has limited the activities of society, including ones of the ecclesial communities. The restrictions have an impact on the participation of parishioners both in their ecclesial activities and in their social involvement. In dealing with this reality, the author explores the idea of a participatory and social-involved Church in which the parishioners can take part both internally in Church life and externally in social activities. The Church must get out of the ritualistic confinement and shift the tendency of pastoral activities that are centered merely on the pastor. The method applied in this study is a qualitative method with data collection techniques using a questionnaire via google form. The author concluded that the participatory Church can be seen in its reputation as a community, communion of community, participatory Church, witnessing Church, and agent of transformation.